Polarization of Stakeholder Orientation Towards Geotourism Development in the Mount Slamet and Serayu Mountainous Areas, Central Java Province - Mafut Munajat; Ricky Avenzora; Dudung Darusman; Sambas Basuni (Institut Pertanian Bogor (IPB University), 2022)
The success of geotourism development is strongly influenced by the orientation (perceptions, motivations and preferences) of the stakeholders. An aim of the study was to analyze the polarization of stakeholder orientation towards geotourism development in the Mount Slamet and Serayu Mountainous areas, Central Java Province. Research instrument used a closed-ended questionnaire following the scoring pattern of